Struggle turning back to professional nursing practice in Iran: A qualitative study - Nooredin Mohammadi; Naiemeh Seyedfatemi; Alireza Nikbakht-Nasrabadi; Mokhtar Mahmoudi (Wolters Kluwer Medknow Publications, 2021)
Background: Current nursing shortage is becoming more complicated because of turnover intention among nurses. Most of the inactive nurses in Iran after a long time for various rations Returned To Professional Nursing Practice (RTPNP). Because the RTPNP program does not exist in Iran to prepare inactive nurses returning to practice, this study aimed to explore the strategies that contribute to preparing nurses for RTPNP. Materials and Methods: The present study was a part of the findings of a larger grounded theory study that lasted about 9 months from April 2019 to December 2019. The data were collected through semi-structured interviews with participants after signing an informed consent form. The average interview duration was 40 minutes. The study participants were selected through purposeful sampling from both public and private hospitals affiliated to Iran University of Medical Sciences. Participants included eight nurses, two education supervisors, two matrons, and two head nurses. Interviews were verbatim transcribed and analyzed using a constant comparative analysis method. Results: Struggle turning back to PNP was the main category that emerged from four categories of "seeking learning resources," "return to practice support," "getting used to a practice," and "building a new family life" from the data analysis process. Conclusions: Returners struggle to get prepared for providing PNP to clients if there is no definite process of RTPNP. Organizational support and RTPNP programs are efficient strategies and could help these returners get prepared for PNP.